Instagram Sebagai Media Komunikasi Pembangunan Pemerintah: Studi Pemenang Penghargaan Pembangunan Daerah Tahun 2022 - Sumarwan, Edi; Kartika, Tina; Fitria, Nurma; Aprilia, Alfaynie Axelfa Tri; Indriani, Atika Nurwan (Institut Pertanian Bogor, 2023)
The West Java Provincial Government won the first Regional Development Award in 2022. In the implementation of development, this government agency actively utilizes Instagram social media as a medium for development communication. West Java Provincial Government has an Instagram account called @jabarprovgoid with 62.1K followers and 6,839 posts. The focus of this research discusses the utilization of Instagram as a development communication media including strategies, types of content posted, and its impact on community participation in achieving development goals. This research is a type of descriptive qualitative research with a content analysis method that uses the unit of analysis of @jabarprovgoid account posts in 2022. Posts were selected based on posts that received the most public attention either from the number of likes or comments from followers. As well as, content that contains messages supporting development. The data obtained is given categorization, then reduced, analyzed, then conclusions are drawn, then presented in the form of tables and descriptions. The results showed that the West Java Provincial Government's use of Instagram as a communication media is to disseminate general information, plans, implementation, and achievements of development programs, increase public participation, promotion of sustainable program innovations, and develop the government's image and reputation. The West Java Provincial Government applies the PCSD strategy to increasing community participation by raising needs, and practical problems in the form of visual message designs that create themes to be discussed by the principles of communication media.